ANALISIS KEPATUHAN MINUM OBAT TB PARU DI WILAYAH KERJA UPTD PUSKESMAS X KOTA PALEMBANG - Chairil Zaman (Universitas Pahlawan Tuanku Tambusai, 2022)
Pulmonary tuberculosis (pulmonary TB) is a chronic infectious disease caused by the bacterium Mycobacterium tuberculosis. Patients with pulmonary tuberculosis require routine treatment for 6-9 months, and in some cases longer. Tuberculosis treatment is divided into an initial (intensive) phase and an advanced phase, where OAT is given in package form to facilitate drug administration and ensure the continuity of treatment until it is finished. The study aimed to see the relationship between variables (age, knowledge, motivation, family support, and support/role of health workers) with adherence to taking pulmonary TB medication in the working area of the UPTD puskesmas x Palembang city. This type of research is a quantitative study with a cross-sectional design. The results showed that of the 36 respondents, 19 respondents (52.7%) had good adherence to taking TB medication, 19 respondents (52.7%) were old, and had good knowledge 21 respondents (58.3%), had good motivation 18 respondents ( 50.0%), good family support 21 respondents (58.3%) and the role of good health workers 20 respondents (55.0%). There is a significant relationship between the Knowledge variable and Compliance with TB Medication (pValue=0.008 < of value α=0.05, OR=6.87). There is a significant relationship between the Variable Motivation and Compliance with Taking TB Medication (pValue=0.019 < of the value α=0.05, OR=5.20). There is a significant relationship between Family Support and Compliance with TB Medication (pValue=0.048 < of value α=0.05, OR=4.00). There is no significant relationship between the role of health workers and compliance with pulmonary TB medication (pValue=0.296 < of value α=0.05, OR=0.491). Keywords: pulmonary TB, compliance